2015 Open Conference of Electrical, Electronic and Information Sciences (eStream) 2015
DOI: 10.1109/estream.2015.7119478
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm for real-time detection of heart rate from noisy ECG signals supported by continuous blood pressure analysis

Abstract: The algorithm proposed in this paper is designed for robust identification of the heart beat annotations in multimodal data, consisting of ECG signal and one or several continuous arterial blood pressure signals. In case the ECG signal is distorted or unavailable the heart beat annotations are detected in continuous blood pressure signal. The novelty of the proposed solution lays in the adaptation of the algorithm for implementation on a real time system, a weighted estimation of the average RR interval in ECG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Table 6 presents the signals that have been employed in the reviewed papers. Most of the proposals for heartbeat detection employ the ECG and ABP signals, since these are directly related with cardiac activity [42,43,44,45,46,47,48,49,50,51,52]. Other authors have added some other signals to that group: PPG signal [53,54]; SV and PPG signals [55]; and EEG, EOG, and EMG signals [56,57].…”
Section: Heartbeat Detection From Multiple Physiological Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 6 presents the signals that have been employed in the reviewed papers. Most of the proposals for heartbeat detection employ the ECG and ABP signals, since these are directly related with cardiac activity [42,43,44,45,46,47,48,49,50,51,52]. Other authors have added some other signals to that group: PPG signal [53,54]; SV and PPG signals [55]; and EEG, EOG, and EMG signals [56,57].…”
Section: Heartbeat Detection From Multiple Physiological Signalsmentioning
confidence: 99%
“…ABP signal quality in References [47,50,55] and BP signal quality in Reference [68] are computed from the SAI, which integrates the pressure ranges and the average derivative for a cycle for the respective signals. The SAI is also employed to assess the ABP signal quality in References [42,46].…”
Section: Heartbeat Detection From Multiple Physiological Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on heartbeat detection from the fusion of multimodal signals have been conducted, and overall reviews of such studies have been reported (Silva et al 2015). Based on the types of signals used for fusion, we can categorize previous studies in two ways: (i) the fusion of cardiovascular signals (Li et al 2007, Tarassenko et al 2010, Abromavicius and Serackis 2015; and (ii) the fusion of cardiovascular with NC signals (Gierałtowski et al 2015, Rankawat andDubey 2017). For studies exploring the fusion of cardiovascular signals, Li et al (2007Li et al ( , 2009 fused ECG with ABP signals, Tarassenko et al (2010) fused ECG with pulse oximetry signals, and Abromavicius and Serackis (2015) fused ECG signals with several continuous ABP leads.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the types of signals used for fusion, we can categorize previous studies in two ways: (i) the fusion of cardiovascular signals (Li et al 2007, Tarassenko et al 2010, Abromavicius and Serackis 2015; and (ii) the fusion of cardiovascular with NC signals (Gierałtowski et al 2015, Rankawat andDubey 2017). For studies exploring the fusion of cardiovascular signals, Li et al (2007Li et al ( , 2009 fused ECG with ABP signals, Tarassenko et al (2010) fused ECG with pulse oximetry signals, and Abromavicius and Serackis (2015) fused ECG signals with several continuous ABP leads. However, these techniques would not give reliable heart-rate estimates if all the fused cardiovascular signals are concurrently noisy.…”
Section: Introductionmentioning
confidence: 99%